1962
DOI: 10.1017/s0022112062001081
|View full text |Cite
|
Sign up to set email alerts
|

On driving a viscous fluid out of a tube

Abstract: Two problems are considered. First, it is shown experimentally that the amount of viscous fluid left on the walls of a horizontal tube, when it is expelled by an inviscid fluid, reaches an asymptotic value of 0.60 of the amount required to fill the tube, when the parameter μU/T is increased, μ and T being the coefficients of viscosity and interfacial surface tension respectively, and U the velocity of the interface between the two fluids. Secondly, by neglecting the inertia terms in the equations of motion and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
101
0
4

Year Published

1972
1972
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(116 citation statements)
references
References 2 publications
(2 reference statements)
9
101
0
4
Order By: Relevance
“…3,[9][10][11][12] This problem was also studied by many researchers experimentally 13,14 and numerically. [15][16][17][18] In miscible core-annular flows, the thickness of the more viscous fluid layer left on the pipe walls and the speed of the propagating "finger" were experimentally investigated by many authors [19][20][21][22][23] and the axisymmetric and "corkscrew" patterns were found. [24][25][26][27][28] In neutrallybuoyant core-annular pipe flows, d'Olce et al 29 observed axisymmetric "pearl" and "mushroom" patterns at high Schmidt number.…”
Section: Introductionmentioning
confidence: 99%
“…3,[9][10][11][12] This problem was also studied by many researchers experimentally 13,14 and numerically. [15][16][17][18] In miscible core-annular flows, the thickness of the more viscous fluid layer left on the pipe walls and the speed of the propagating "finger" were experimentally investigated by many authors [19][20][21][22][23] and the axisymmetric and "corkscrew" patterns were found. [24][25][26][27][28] In neutrallybuoyant core-annular pipe flows, d'Olce et al 29 observed axisymmetric "pearl" and "mushroom" patterns at high Schmidt number.…”
Section: Introductionmentioning
confidence: 99%
“…The interface between the two fluids becomes unstable, forming Kelvin-Helmholtz (KH) instabilities and 'roll-up' structures (Joseph et al 1997;Sahu et al 2009a,b). Experimental studies in miscible core-annular flows (Taylor 1961;Cox 1962;Chen & Meiburg 1996;Petitjeans & Maxworthy 1996;Kuang, Maxworthy & Petitjeans 2003) have focused on analysing the thickness of the more viscous fluid layer left on the pipe walls and the speed of the propagating 'finger' tip. The development of different instability patterns, like axisymmetric 'corkscrew' patterns, in miscible flows has also been investigated (Lajeunesse et al 1997(Lajeunesse et al , 1999Scoffoni, Lajeunesse & Homsy 2001;Cao et al 2003;Gabard & Hulin 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies involving channel flows have demonstrated the destabilising effect of diffusion for continuous but rapidly varying viscosity stratification [30]. In the case of core-annular miscible flows, some experimental studies have focused on determining the thickness of the more viscous fluid left on the pipe walls following its displacement by a less viscous fluid and on measuring the tip speed of the propagating 'finger' of the latter [31][32][33][34][35][36]. Others works have examined the development of 'interfacial' axisymmetric and "corkscrew" patterns that accompany these flows [2,[37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%